2009
DOI: 10.1161/circulationaha.109.855817
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Entering the Metabolic Syndrome

Abstract: Particular trajectories and combinations of factors on entering the MetS confer higher risks of incident cardiovascular disease and mortality in the general population and among those with MetS. Intense efforts are required to identify populations with these particular combinations and to provide them with adequate treatment at early stages of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 19 publications
8
117
2
1
Order By: Relevance
“…Dyslipidemia has been reported to precede the appearances of blood pressure elevation, fasting glucose elevation, and WC enlargement, 43 and BF% has been suggested to be superior to BMI for detecting subjects with dyslipidemia in a previous study. 44 In the presence of a positive net energy balance, there is increased accumulation of triglycerides in both adipose tissues and non-adipose tissues, such as muscle and liver.…”
Section: Discussionmentioning
confidence: 88%
“…Dyslipidemia has been reported to precede the appearances of blood pressure elevation, fasting glucose elevation, and WC enlargement, 43 and BF% has been suggested to be superior to BMI for detecting subjects with dyslipidemia in a previous study. 44 In the presence of a positive net energy balance, there is increased accumulation of triglycerides in both adipose tissues and non-adipose tissues, such as muscle and liver.…”
Section: Discussionmentioning
confidence: 88%
“…T he metabolic syndrome and its components are significant cardiovascular risk factors [1][2][3] and occur disproportionately in racial/ethnic minorities in the United States. 4 Although the definition of the metabolic syndrome may be clinically useful, 5 its genetic architecture remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have actually shown that abdominal obesity more strongly associated with cardiovascular heart diseases (CHD) (Singh et al 2010). Excess abdominal fat is associated with hyperinsulinism and cardio-metabolic alterations (Freedman et al, 2007;Franco et al 2009). The complex relation between body weight and morbidity and mortality was reflected in recent publication from the US National Center for Health Statistics (Flegal et al 2007).…”
Section: Discussionmentioning
confidence: 99%